Reusability and leakage of immobilized laccase enzyme - Lau Chin Yee, Cindy (2015)
Laccase (EC 1.10.3.2, benzenediol: oxygen oxidoreductase), a copper containing enzyme which can catalyse the oxidation of various organic and inorganic substrates, is usually used to decolorize the wastewater effluent and render phenolic compounds to less toxic component. The objective of this research is to compare the reusability and leakage between entrapped and covalently bonded laccase enzymes. The reusability of immobilized laccase enzyme was studied by reacting a batch of immobilized laccase enzymes with ABTS repeatedly for 15 cycles. The study of the leakage of immobilized laccase enzyme was carried out by storing the immobilized laccase enzymes in acetate buffer solution for 32 days. The acetate buffer solution samples were taken and reacted with ABTS. The samples reacted with ABTS were analysed using a UV-Vis spectrophotometer at 415 nm. The absorbance readings were recorded and enzyme activities were calculated. The data collected showed that the retained enzyme activities of entrapped and covalently bonded enzyme after being reused for 15 cycles are 33.50% and 48.19% respectively. On the other hand, the leakages of entrapped and covalently bonded laccase enzyme after 32 days are 13.9 % and 14.46 % respectively. In conclusion, the covalently bonded laccase enzymes are more stable in terms of reusability and storage stability compared to entrapped laccase enzymes.